ABO4 type scheelite phases in (Ca/Sr)MoO4 - BiVO4 - Bi2Mo3O12 systems: synthesis, structure and optical properties - Z. A. Mikhaylovskaya (Uralʹskij federalʹnyj universitet imeni pervogo Prezidenta Rossii B.N. Elʹcina, 2021)
The cation deficient complex oxides of (Ca/Sr)MoO4 - BiVO4 - Bi2Mo3O12 triple system are promising photocatalysts and pigments. Compounds with general formula of Ca1−1.5x-yBix+yФxMo1-yVyO4  and Sr1−1.5x-yBix+yФxMo1-yVyO4 were synthesized byconvention solid state technique in the range of 550–720 °C. Two wide regions of the solid solutions (ordinary and superstructured scheelite-type phases respectively) were found for each system. The diffuse scatering of homogeneous samples was investigated in the range of 190–1100 nm. Energy gaps calculated with linear approximation of Kubelka-Munk function decreases with bismuth and vanadium content.